Design of a soft-contact triboelectric nanogenerator for vibrational energy collection and its output performance - Yan, Jin; Mei, Naerduo; Zhang, Dapeng; Zhong, Yinghao (Frontiers in Energy Research, 2022)
Finding renewable energy sources to lower carbon emissions has emerged as a challenge the world faces in the wake of global warming and energy crises. Vibration is a type of mechanical motion common in daily life, and one popular research topic in this regard is how to gather vibrational energy and transform it into electricity. Vibration energy can be collected using triboelectric nanogenerators whose working mechanism is based on contact electrification and electrostatic induction. The COMSOL software is used to simulate the relationship between the voltage across electrodes, transferred charge, and the electrode moving distance (V-Q-X) of triboelectric nanogenerator. Theoretical analysis of the simulation result is offered, along with a brief description of the simulation procedure. When wool is glued to the inner core aluminum foil, TENG’s output performance is significantly improved, with a maximum open-circuit voltage of 160 V. In addition, TENG’s output performance improves linearly as the vibration frequency and amplitude increase. Specifically, when the vibration frequency rises from 1 to 2.5 Hz, the open-circuit voltage rises from 43 to 100 V, the short-circuit current increases from 0.45 to 1.5 µA, and the peak transfer charge grows from 23 to 46 nC; when the vibration amplitude increases from 30 to 60 mm, the maximum open-circuit voltage increases from 50 to 110 V, the maximum short-circuit current increases from 0.3 to 1.5 µA, and the maximum charge transfer increases from 21 to 54 nC. Durability tests of TENG shows that the soft-contact TENG with wool adhesives is exceptionally durable, with decreased mechanical wear on the contact surface and extended service life. The present work is expected to provide some insight into the working mechanism of low-loss and high-performance TENGs and facilitate their wider adoption.